MODEL PROGRAM PENINGKATAN MUTU GURU BERBASIS KEBUTUHAN - Dwi Esti Andriyani (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Teacher quality is one of important factors for good education.Therefore, it is a demand to develop and implement effective qualityteacher improvement programs. Effective quality teacher improvementprograms should be based on need assessments. This study aims todescribe teacher quality improvement programs based on teachers’needs by studying: 1) the profile of Junior High School teachers inBanyumas which includes several teachers’ aspects: their career rank,their academic qualification, and their mastery of teachercompetencies; 2) teachers’ opinions of teacher quality improvementprograms, and 3) teacher quality improvement programs based onteacher needs.This is a survey research of 607 Junior High School teachers whowere selected randomly. The research was conducted in Banyumas.The study employed opened and closed questionarries to collect data.The data analysis applied quantitative descriptive technique.The profile of Junior High School teachers in Banyumas show thatnone of teachers has been in IV/b career rank. However, most ofteachers have met the academic qualification requirement. Only a fewteachers hold Senior High School and D3 certificate and haveirrelevant education background with the subjects that they teach. Theteacher mastery of teacher competencies which are pedagogieccompetency, professional competency, and scientific writingcompetency is fair. There are two programs needed to improve thequality of Junior High School teachers in Banyumas: 1) program toimprove teacher’s academic qualification, and 2) program to improveteacher’s competency. Teacher academic qualification improvementprogram based on teachers’ needs should consider following aspect; itshould consist of undergraduate programs, D3 and S1, and graduateprogram: S2. 2) The study program should be in education field andrelevant with the subjects that teachers teach. 3) The program shouldtake place near or within location in which teachers live. 4) Theprogram need to provide supports for teachers such as funding forstudying – tuition fee and operational costs-, and study permit ordispensation to be free of or have only few teaching hours. Severalaspects also should be considered in the implementation of teachercompetency improvement program. According to teachers, training is the most suitable form to improve their competency besides workshop,seminar, and shortcourse (1-3 months). The programs should addressa) teacher competency in subject matters which is needed by most ofteachers, b) teacher competency in teaching, and also c) teachercompetency in making a scientific writing. Implementing program in alocation where teachers live in will be very helpful for teachers.Besides that, teachers need some supports such as money and alsopermit to join the program.